Role of Industry Players in Brunei's Halal Industry Development - Rahim, Siti Majidah; Sulaiman, Nor Surilawana (KnE Social Sciences, 2023)
The global halal market is a substantial and expanding consumer market, both domestically and internationally. With the projected increase in the world’s Muslim population by 35% by 2030, reaching 2.2 billion, the demand for halal products is expected to soar, potentially reaching USD 6.0 trillion by 2024. Brunei holds great potential to become a prominent halal hub worldwide and offer its high-quality local halal brand to the global market, contingent on the government’s concerted efforts to foster the growth of the halal industry in the country. To understand the role of industrial players in Brunei, this study aims to assess their impact, particularly considering the challenges they face in influencing the government’s direction in the country. Through an online survey, 150 respondents, who specialized in Bachelor of Halal Science, provided additional insights on the significance of industry players in shaping the development of Brunei’s halal industry. The majority of respondents believe that industry players play a significant role alongside policymakers and the Brunei government in reinforcing and continuously enhancing the nation’s halal standards, laws, and regulations. Keywords: Brunei, government, halal industry, industry development, industry players